Development of Problem-based Learning LKPD to Improve Student Understanding - Wahyuni, Putri; Suasti, Yurni; wati, Erna (International Journal of Educational Dynamics, 2024)
Textbooks are a vital component in the educational process, serving as essential teaching materials that aid students in achieving learning objectives and competency standards. Teachers face challenges in choosing and determining appropriate learning models, but teaching materials offer solutions to address classroom issues. These materials can be sourced from personal experience, expert opinions, colleagues, books, mass media, the internet, and more. Teaching materials facilitate students' engagement with real-life facts and experiences, enabling them to assess and develop ideas, solve problems, acquire skills, and nurture creativity. Teaching materials encompass a wide range of formats, including printed resources (such as workbooks, modules, and learning comics), audio resources (such as sound recordings), audio-visual resources (such as educational videos and cartoons), and interactive materials (such as e-workbooks and web-based resources). The success of the learning process hinges on the careful selection and development of suitable teaching materials. This development is part of scientific research aimed at creating or improving products with practical value. Nana Syaodih Sukmadinata supports this perspective, emphasizing that research and development involve steps to create new products or enhance existing ones. In summary, teaching materials play a crucial role in educational success by providing students with valuable experiences and supporting the curriculum effectively.